Case Report: Exostosin 1-associated membranous nephropathy and Guillain-Barré syndrome: a common autoimmune etiology? - León-Póo, Mariana; López-Melero, Eva; Shabaka, Amir; Guerrero-Márquez, Carmen; Barcenilla-López, María; Cases-Corona, Clara; Gruss, Enrique; Roldán, Deborah (Frontiers in Nephrology, 2025)
Membranous nephropathy is one of the most common causes of nephrotic syndrome in adults and is caused by the deposition of immune complexes in the subepithelial space of the glomerular basement membranes. On the other hand, Guillain-Barré syndrome is a type of acute, potentially fatal polyneuropathy, which is generally associated with an infection that serves as the initial immunological event and triggers immune-mediated disruption of the axon and/or myelin. We present the case of a 70-year-old patient with concurrent membranous nephropathy and Guillain-Barré syndrome, with subepithelial deposits in the renal biopsy positive for Exostosin 1, and who reached complete renal remission after treatment of Guillain-Barré syndrome with plasmapheresis and systemic corticosteroids, suggesting a common autoimmune origin for both entities.